The Effect of the Jigsaw Type Cooperative Learning Model on Students’ Conceptual Understanding of Collisions Material - Lalu Azikri Amrullah; Mahrus Mahrus; Gunawan; Kosim; Audy Sintia Anugraheni; Erika Lestari (Indonesian Journal of Educational Innovation, 2026)
Low understanding of physics concepts is often caused by learning models that do not facilitate active student interaction in the dissection of abstract phenomena. This study aims to analyze the effect of implementing the Jigsaw-type cooperative learning model on students’ conceptual understanding of collision material at MA Nurul Iman. The method used was a quasi-experimental design with a Nonequivalent Control Group Design, involving the experimental class of 21 students and the control class of 20 students. The results of the data analysis using the Independent Samples T-Test showed a significance value of 0.000, indicating a significant difference in achievement between the two groups. The increase in conceptual understanding in the experimental class reached an N-gain score of 0.76 (High category), surpassing that of the control class, which achieved 0.56 (Medium category). The Jigsaw model is significantly more effective at improving students’ cognitive quality than the conventional model, thanks to individual responsibility mechanisms and peer tutoring. These findings contribute to the development of active learning strategies in secondary schools. Recommendations for educators to integrate cooperative models to overcome visualization barriers in complex mechanical concepts.